Entity Framework, uma introdução ao ORM utilizando o Code First - Alcaraz, Paulo Cesar Fernandez (2016)
To minimize the problem of communication between the relational database and object-oriented programming, use Object-relational Mapping tools, whose goal is to enable transparent communication between the application and its data pack. The Entity Framework is Microsoft's ORM (Object-Relational Mapping) that makes that communication between these two different models, reducing programming time, focusing on the development and business rules. This work demonstrates the use of this ORM, creating the database, your relationships, database information shipments and customizing tables using the Code First in C # with POCO (Plain OLD CLR Object) classes.